The Association between Coffee Consumption Pattern and Prevalence of Metabolic Syndrome in Korean Adults - Kim, Seong-Ah (Nutrients, 2019)
The inconsistent results of epidemiologic studies suggest that the health effects of coffee vary depending on coffee consumption pattern, such as the type and amount of coffee intake. This study investigated the association between coffee consumption and metabolic syndrome (MetS) in Korean adults. In total, coffee consumption patterns in 14,132 participants were assessed based on two-day, 24-h recall data. Multivariable logistic regression was used to examine the association between the type and daily servings of coffee and the prevalence of MetS. In women, the prevalence of MetS (odds ratio (OR) 0.82; 95% confidence interval (CI): 0.70, 0.96), elevated triglycerides (0.85; 0.75, 0.97), and reduced high-density lipoprotein (HDL)-cholesterol (HDL-C; 0.74; 0.66, 0.83) in 3-in-1 coffee consumers, as well as the prevalence of increased waist circumference (0.81; 0.68, 0.98) and reduced HDL-C (0.68; 0.59, 0.80) in black coffee consumers, were significantly lower compared to non-coffee consumers. Also, the inverse associations between total coffee intake, black coffee intake, and 3-in-1 coffee intake with MetS or components of MetS were more significant in individuals who consumed >1 versus ≤1 serving/day. In conclusion, coffee consumption (regardless of type) was associated with a reduced prevalence of MetS and its components in Korean women.